Pengaruh Recruitment dan Pengalaman Kerja Terhadap Prestasi Kerja Dengan Penempatan Kerja Sebagai Variabel Intervening Pada Rumah Sakit Tingkat III Dr. Reksodiwiryo Padang - Citra Faras Fadhilah; Marta Widian Sari; Nila Pratiwi (Lembaga Pengembangan Kinerja Dosen, 2024)
The aim of this research is to measure the influence of Recruitment and Work Experience on Job Performance, with Job Placement as an Intervening Variable, at Level III Dr. Hospital. Reksodiwiryo Padang. The population is all employees, with a sample of 64 respondents using quantitative and survey methods. Data was collected through questionnaires. Analysis uses Structural Equation Modeling (SEM) with Partial Least Square (PLS). The results show a fairly good influence, with Recruitment not being significant on Job Performance, while Work Experience has a positive and significant influence on Job Placement and Job Performance. Another finding is that Recruitment is not significant to Job Placement, and Work Experience is not significant to Job Placement through Job Performance. In conclusion, Work Experience has a significant impact in improving Job Placement and Job Performance at Dr. Hospital. Reksodiwiryo Padang.